2009
DOI: 10.1089/lap.2008.0121.supp
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Track Surgery of the Colon in Children

Abstract: Minimally invasive surgery is safe and effective in pediatric colonic surgery and allows a fast recovery time (fast-track).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 11 publications
2
15
0
1
Order By: Relevance
“…Similarly, a study by Mattioli et al. 23 in 2009 showed that good bowel movement, rapid mobilization, and early feeding can be achieved by avoiding the use of drains, nasogastric tubes, and urinary catheters and by achieving acceptable pain control and limiting the use of systemic opioid drugs. Therefore, a combination of multimodal perioperative interventions rather than a single intervention on its own might contribute to more rapid postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study by Mattioli et al. 23 in 2009 showed that good bowel movement, rapid mobilization, and early feeding can be achieved by avoiding the use of drains, nasogastric tubes, and urinary catheters and by achieving acceptable pain control and limiting the use of systemic opioid drugs. Therefore, a combination of multimodal perioperative interventions rather than a single intervention on its own might contribute to more rapid postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of studies have evaluated the role of ERAS in pediatric surgery in general. Surgical procedures that have been studied include appendectomies, hypospadias repairs, nephrectomies, pyloromyotomies, fundoplications, ileocecectomies, and bowel surgeries requiring anastomoses [10][11][12][13][14]. Most of these studies did demonstrate a reduction in hospital length of stay when the ERAS protocol was implemented.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the efficacy of laparoscopic colectomy has been demonstrated in a number of elective conditions, including inflammatory bowel disease, familial polyposis, and rare congenital anomalies [9][10][11][12]. In the developed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the safety and efficacy of elective laparoscopic surgery for benign lesions of colon and rectum are well documented [9][10][11][12]. However, the role of laparoscopic surgery for urgent and emergent colectomy in children has never been described.…”
Section: Introductionmentioning
confidence: 99%